Quality Control of Hybrid Corn Seed Production Using Six Sigma Methode - Wahyuni, Cici Nuraini; Hidayat, Syarif Imam; Indah, Pawana Nur (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
Advanta Seeds is a company engaged in sustainable agriculture with a production focus on hybrid corn seeds. In the processing of corn seeds, PT. Advanta seeds Indonesia experiences a high average product defect 10% of the total production. Therefore, the purpose of this research is to analyze the quality control od hybrid corn seeds using the six sigma method and seek continuous improvement actions. In this research using step define, measure, analyze, improve, and control. Data collection in April – May 2023 and September – November 2023 by production recapitulation. The results showed that the company’s sigma level was 3,40, meaning that in the production process improvement was still. There are three types of defect in corn seeds production : non-conforming corn cobs, seeds that do not match the size and damage seed. Non-conforming cobs are the most dominant type of defect caused by human, environment, and raw material factor. The continuous improvement action such as conducting stricter supervision during male flower detaseling activities, providing training when there are new hybrid of varieties. After taking corrective action there is an increase in the capability of the production process (Cpk > 1,00) so that it can be said to be capable